The Effect Of Visa Exemption Policy On Indonesian Export - Malewa, Banga; Yudhistira, Muhhamad Halley (Jurnal Ekonomi Kuantitatif Terapan; Vol 17 No 1 (2024): Vol. 17, No. 1, Februari 2024 (pp.1-154)DO - 10.24843/JEKT.2024.v17.i01.p01, 2024)
This study examines the effect of the visa exemption policy on Indonesia’s exports, by using Staggered Difference in Difference (DID) method and Indonesia's export data to 191 partner countries in 2015 - 2019 period. This study finds that visa exemption policy of Indonesia has effect on its export, but it is not "one size fits all". A significant positive effect was generated by visa-exemption received by American region, and a significant negative effect on exports was generated by visa exemption received by Oceania region. American region is one of the priority recipients of visa exemption policy of Indonesia, and provides the most visa exemption to Indonesia after the Asian region. Meanwhile, Oceania is the most restricted region in terms of visa exemption policy both unilaterally or reciprocally with Indonesia.   Keywords: Visa Exemption, International Trade, Export, Staggered DID JEL Codes: F13, F16, F22